2020
DOI: 10.1007/s00432-020-03330-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of niclosamide and temozolomide against human glioblastoma tumorspheres

Abstract: Purpose Glioblastoma (GBM) is the most aggressive type of brain tumor and has poor survival outcomes, even after a combination of surgery, radiotherapy, and chemotherapy. Temozolomide is the only agent that has been shown to be effective against GBM, suggesting that combination of temozolomide with other agents may be more effective. Niclosamide, an FDA approved anthelmintic agent, has shown anti-cancer effects against human colon, breast, prostate cancers as well as GBM. However, the efficacy of the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…We then zeroed in on niclosamide, a previously FDA-approved drug that has been widely used in humans for tapeworm treatment for decades. In addition to its excellent pharmacokinetic/dynamic (PK/PD) properties and safety profile (27, 3739), niclosamide exhibits outstanding protective effects against cisplatin- and noise-induced hearing loss in both zebrafish and mice when administered systemically. In summary, our work highlights that 1) by using the CMap it is possible to identify compounds that can regulate biological pathways associated with various pathogenic conditions including acquired hearing loss; 2) FDA-approved drugs can be repurposed to prevent cisplatin- and noise-induced hearing loss in clinics; and 3) by targeting multiple biological pathways (3739) rather than individual pathways, niclosamide can exert better protection than targeting individual pathways against acquired hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We then zeroed in on niclosamide, a previously FDA-approved drug that has been widely used in humans for tapeworm treatment for decades. In addition to its excellent pharmacokinetic/dynamic (PK/PD) properties and safety profile (27, 3739), niclosamide exhibits outstanding protective effects against cisplatin- and noise-induced hearing loss in both zebrafish and mice when administered systemically. In summary, our work highlights that 1) by using the CMap it is possible to identify compounds that can regulate biological pathways associated with various pathogenic conditions including acquired hearing loss; 2) FDA-approved drugs can be repurposed to prevent cisplatin- and noise-induced hearing loss in clinics; and 3) by targeting multiple biological pathways (3739) rather than individual pathways, niclosamide can exert better protection than targeting individual pathways against acquired hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Niclosamide has been used safely for nearly 40 years since 1982 for the treatment of parasitic infections in humans (20, 27, 28). Although it has been discontinued in the US due to commercial reasons, it represents an excellent opportunity to repurpose this FDA-approved drug for new indications such as treatment for cancers and hearing loss (37, 48, 49). Niclosamide has many desirable drug properties: (a) it is effective by itself against colon metastatic tumors such as HCT116, SW620, LS174T, SW480, and DLD-1 and is synergistic with cisplatin in a xenograft mouse model of renal cell carcinoma through Wnt/β-catenin signaling (20, 30), it can be delivered orally, which is a significant advantage over other local delivery methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, niclosamide was demonstrated to reverse enzalutamide resistance in prostate cancer cells [ 28 ]. Oh et al [ 29 ] recently reported that combined treatment with both niclosamide and temozolomide can significantly reduce cell viability, stemness and suppress the invasive capabilities of GBM tumorspheres [ 29 ]. In our previous study, it was also shown that niclosamide can promote cytotoxicity in human glioblastoma cells by downregulating the pro-survival PI3K/AKT, STAT3 and Wnt/β-catenin signal pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Summary of the repurposed drugs for BC discussed in the chapter.Breast Cancer Drug Repurposing a Tool for a Challenging Disease DOI: http://dx.doi.org/10.5772/intechopen.101378 clinical application diseases include type 2 diabetes, endometriosis, neuropathic pain, bacterial and viral infections, including cancer[77]. The anticancer benefits of niclosamide have been shown in many malignancies such as colon cancer, lung cancer, prostate cancer in humans, as well as breast cancer by suppressing various cancer related pathways such as Wnt Notch, mTOR, STAT, and NFκB[78,79]. The combinational treatment of niclosamide with cisplatin overcomes the resistance to cisplatin and induces an inhibitory effect on proliferation in vitro and reduced tumor size in vivo.…”
mentioning
confidence: 99%